2016
DOI: 10.1111/jvim.13931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 0.5% Timolol Maleate Ophthalmic Solution on Heart Rate and Selected Echocardiographic Indices in Apparently Healthy Cats

Abstract: BackgroundEchocardiographic assessment of diastolic function is challenging in cats, partially because of transmitral flow pattern fusion associated with high heart rates. With heart rate (HR) reduction, transmitral flow waveforms separate, allowing identification of diastolic dysfunction. Timolol, an ophthalmic, nonselective beta‐blocker used in glaucoma is safe and transiently decreases HR in clinical trials.HypothesisAdministration of timolol ophthalmic solution decreases HR and facilitates echocardiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…The timolol group was composed of 33 cats, including 18 females (mean age 6.1 years [range 1-13]; mean weight 5.1 kg [range 2. [1][2][3][4][5][6][7][8][9][10][11]). This group included Persian (n = 2), Maine Coon (n = 1), Siamese (n = 1) and mixed breed (n = 29) cats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The timolol group was composed of 33 cats, including 18 females (mean age 6.1 years [range 1-13]; mean weight 5.1 kg [range 2. [1][2][3][4][5][6][7][8][9][10][11]). This group included Persian (n = 2), Maine Coon (n = 1), Siamese (n = 1) and mixed breed (n = 29) cats.…”
Section: Resultsmentioning
confidence: 99%
“…The mean decrease of 30 bpm was close to that previously reported (25 bpm). 11 Interestingly, another research group reported that a drop of timolol gel-forming solution did not affect HR 4 and 8 h later, 34 suggesting the bradycardic effect may not last long.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,41,42 If the E and A waves are summated, one can wait for the heart rate to come down as the cat relaxes over time, can apply a vagal maneuver, such as pressing on the nasal planum, or can administer a low dose of a beta blocker, such as ocular timolol, to slow the heart rate. 45,46 Tissue Doppler interrogation of the mitral valve annulus can also be performed and should show a reduced E' wave velocity. 47 Thoracic radiographs in dyspneic cats that have RCM show a higher occurrence of PLE (59%) than PE (25%) but both can be present (16%).…”
Section: Diagnosismentioning
confidence: 99%